Perancangan Pembangkit Listrik Tenaga Surya On-Grid Di Gedung Lembaga Penelitian Dan Pengabdian Kepada Masyarakat UKI-Jakarta Menggunakan Aplikasi PVSyst - Tukan, Blasius Rum; Widodo, Bambang; Purba, Robinson (Lektrokom : Jurnal Ilmiah Teknik Elektro, 2023)
The PLTS designed in the LPPM UKI-Jakarta building is an on-grid PLTS with the aim of lowering electricity bills. In analyzing this design, both from a technical and economic perspective, the PVSyst application tool was used. The intensity of solar radiation at the study site is 1654.1 kWh/m2 per year and the electrical energy that can be generated is 17,726 kWh/year using solar modules, a capacity of 10,675 Wp. Savings in the cost of paying for electricity using PLTS amounted to IDR 15,953,400 and the break even point of PLTS is 9.64 years, calculated after construction has been carried out. The construction of this PLTS also reduces CO2 emissions in Jakarta, due to the use of electricity from fossil fuels by 158.1 tons for 25 years. Based on the simulation results and engineering economic calculations from the PLTS being built, a reduction in the cost of using electricity was found to be 50% of the total cost of paying for electricity each year.